Management, Growth, and Carbon Storage in Miombo Woodlands of Tanzania - Z. J. Lupala; L. P. Lusambo; Y. M. Ngaga (International Journal of Forestry Research)
Despite the local livelihoods support function provided by miombo woodlands of Tanzania under participatory forest management, its growth still has potential for carbon storage and sequestration attractive to REDD+ initiatives. This study has revealed the average growth to be significant, despite the local community livelihoods support function. However, climate change mitigation strategy needs to be more innovative to optimize carbon storage and local livelihoods’ potentials in forest-dependent communities like miombo woodlands. Carbon credits resulting from the increased carbon stock and sequestration should contribute to sustainable development. This should also help promote participatory forest management and secure miombo woodland products and services upon which billions of people depend.